Socioeconomic Differences in Smoking and Cessation Across a Period of Rapid Economic Growth in an Upper-Middle-Income Country - Mariapun, Jeevitha; Hairi, Noran Naqiah; Ng, Chiu Wan (Oxford University Press, 2018)
Introduction: Higher smoking rates and lower cessation rates among the poor compared to the rich are evident in high-income countries. In low and middle-income countries (LMICs), many of which are in the early stages of tackling the tobacco epidemic, more knowledge is required of the socioeconomic inequalities in smoking. This is especially the case for upper-middle-income countries, where smoking prevalence is highest. This study examines trends in the socioeconomic gradient in smoking and cessation among adults across a period of rapid economic development in Malaysia, an LMIC with an upper-middle-income economy. Methods: The socioeconomic trends in smoking were analyzed using data from cross-sectional National Health and Morbidity Surveys for the years 1996, 2006, and 2011. Household per capita income was used as a measure of socioeconomic position. As a measure of inequality, the concentration index that quantified the degree of socioeconomic inequality in a health outcome was computed. Smoking was assessed in current and former smokers. The study population was examined by gender, region, and age group. Results: This study found a trend of an increasingly higher smoking prevalence among the poor and higher cessation rates among the rich. With the exception of younger women in Peninsular Malaysia, the socioeconomic gradient in current smoking is concentrated among the poor. For former smokers, especially men, distributions across the years were mostly concentrated among the rich. Conclusion: It is important to ensure that health policies, programs, and interventions consider the potential impact of the socioeconomic patterning in smoking on equity in health. Implications: Findings on the socioeconomic gradient in smoking and cessation from Malaysia across a period of rapid economic development will contribute to addressing the paucity of knowledge on the socioeconomic gradient of smoking and cessation in other progressing LMICs. This study provides evidence from an upper-middle-income country, of an increasing trend of smoking among the poor and an increasing trend of cessation rates among the rich, particularly for men. We found opposing trends for younger adult women in the more developed, Peninsular Malaysia. More rich young women were found to have taken up smoking compared to socioeconomically less advantaged young women. © 2018 The Author(s).